1964
DOI: 10.3181/00379727-115-29052
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Plasma Aldadiene Levels and Antimineralocorticoid Effects of Spironolactone in the Laboratory

Abstract: 7should be looked for in such patients, since, if present, its correction might prolong life so that measures directed toward the underlying process of endotoxin shock could be effective.Summary. An immediate and progressive fall in blood glucose level occurs in CC14treated guinea pigs given a lethal dose of bacterial endotoxin. The hypoglycemia is evidently due to a decrease in rate of hepatic glucose production. Maintenance of the blood sugar level appears to prolong survival but does not alter the extreme s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…The mean and SEM results in the 12 subjects for sodium excretion, potassium excretion, Na/K ratio, log 10 10 Na/K, and urine volume are shown in Table I. This table also shows the significance levels for tests of linearity of the log dose-response trends, for the slope of the log dose-response trends, and for tests of parallelism of the log dose-responses of the two drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean and SEM results in the 12 subjects for sodium excretion, potassium excretion, Na/K ratio, log 10 10 Na/K, and urine volume are shown in Table I. This table also shows the significance levels for tests of linearity of the log dose-response trends, for the slope of the log dose-response trends, and for tests of parallelism of the log dose-responses of the two drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stages of evaluation of prorenoate, we wished, for safety reasons, to observe the effects of single doses of the drug before proceeding to repeated dosing. Kagawa and his coworkers 10,11 have shown that dose-response curves can be obtained using single doses of spirolactones in laboratory animals, and that this method of bioassay yields valid estimates of relative potency for these drugs. We 17 and others 20 have shown that the procedure of Ross 18 can be adapted to allow testing of single doses of aldosterone antagonists in normal man.…”
mentioning
confidence: 99%
“…The two drugs must have a relative potency or, if this assumption is incorrect, the hypothesis that canrenone is responsible for the activity of both drugs must be rejected. (Kagawa et al, 1964). These workers treated rats and dogs with spironolactone and canrenone at doses which yielded similar levels of canrenone in plasma, and simultaneously measured the potency of the compounds in reversing the renal effects of deoxycorticosterone acetate.…”
Section: Discussionmentioning
confidence: 99%
“…The 7a-acetylthio substituent is removed completely from 80% of the administered dose (Sadee, Dagcioglu & Schr6der, 1973) yielding canrenone (other names: aldadiene, SC-9376) (Figure 1) as the principal non-conjugated metabolite in plasma. Canrenone is active as a mineralocorticoid antagonist in animals (Kagawa, Bouska & Anderson, 1964) and has been proposed as the principal pharmacologically active agent after administration of spironolactone to man (Sadee, Dagcioglu & Schr6der, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…From a study of subjects receiving spironolactone who had reached a steady state, Ramsay et al (1977) concluded that canrenone was the principal active metabolite of spironolactone. Conversely, in assessing the antimineralocorticoid activity of a single dose of spironolactone it has been shown that spironolactone was significantly more potent than predicted from the plasma canrenone levels both in human subjects (Ramsay et al, 1976) and animals (Kagawa, Bouska & Anderson, 1964). Furthermore, with a more selective chromatographic assay for canrenone (Dahlof et al, 1979;Ashbagen et al, 1979) the contribution of canrenone to the antimineralocorticoid effect of spironolactone is substantially lower than previously assumed from the fluorimetric method of Gochman & Gantt (1962).…”
mentioning
confidence: 99%